Urgensi Bimbingan Perkawinan Bagi Calon Pengantin Dalam Mewujudkan Keluarga Harmonis - Alfarisi, Usman; Zakaria, Endang; Nurhadi, Nurhadi; Karimah, Ummah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
One of the goals of marriage is to create a harmonious family. The process of realizing a harmonious family requires the attitude of the married couple in living a household life. So the need for marriage guidance for prospective brides. In this study, researchers describe that with the urgency of marriage guidance for prospective brides followed by prospective brides, it is hoped that it will make a harmonious family so that it can form a family that can realize the defense of its family and can face and solve problems in the mahligai household. The method in this research uses a qualitative approach to the literature study method. The result of this study is that from the marriage guidance of prospective brides conducted by the two prospective spouses has urgency in realizing the household mahligai that every individual desires, namely a harmonious family, where families can get peace, comfort, compassion, and love and others. Keywords: Marriage Guidance, Bride-to-be, Family, Harmony